Pengetahuan Masyarakat Desa Dajan Peken terhadap Pengelolaan Sampah Berbasis Sumber - Laksmiwati, Ida Ayu Alit; Wedasantara, Ida Bagus Oka; Budarsa, Gede (Mahesa Research Center, 2024)
Rapid population growth in urban areas has a significant impact on environmental quality, especially in waste management. Waste-related problems are a global concern, not only limited to urban centers, but also spreading to rural areas which require joint efforts. Responding to Bali Province's waste management directives, Dajan Peken Village in Tabanan Regency has started a waste management initiative involving the community. This research aims to assess the condition of waste in Dajan Peken Village which originates from various community activities and explore community knowledge about managing their household waste. The findings show that waste in this village comes not only from households but also from markets, kiosks, offices, schools and places of worship. Even though the community already has fairly good knowledge, ongoing outreach efforts and promotion of the 3R movement are still needed. This research provides localized insights, emphasizing the importance of sustainable waste management practices.